Emotions Behind the Wheel: Customer Incivility, Need Satisfaction, and Service Quality in Online Transportation - Fitri Ramadhani; Febzi Fiona (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study is motivated by the rapid development of digital transportation services, which not only demand system efficiency but also involve emotional dynamics in service interactions. Customer incivility has the potential to influence service quality through users’ psychological mechanisms. Therefore, this study aims to examine the effect of customer incivility and service convenience on service quality by incorporating the mediating role of need satisfaction and the moderating role of surface acting. This study employs a quantitative approach with a causal explanatory design, involving 350 active Maxim users in Indonesia selected through purposive sampling. Data were collected through an online survey and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that customer incivility negatively affects need satisfaction and service quality, while positively influencing surface acting. In addition, need satisfaction and service convenience significantly enhance service quality. Need satisfaction also serves as a mediator, while surface acting moderates the relationship between customer incivility and both need satisfaction and service quality. In conclusion, service quality in digital contexts is shaped by both psychological and functional factors, highlighting the importance for service providers to simultaneously manage emotional experiences and service convenience